Implementation of Stad Cooperative Learning Model to Improve Science Learning Outcomes of Grade VI Students at Sd Negeri 37 Bengkulu City - Kusuma, Try; Apriani, Ria; Hotnida, Denny (Indonesian Journal of Pedagogy and Teacher Education, 2024)
This study aims to improve the learning outcomes of grade VI students in Science learning through the STAD (Student Teams Achievement Divisions) model at SD Negeri 37 Bengkulu City. This research is a Classroom Action Research (CAR) conducted in four stages: planning, implementation, observation, and reflection. The subjects of the study were 32 students in grade VI. Data collection techniques included observation, documentation, and tests. The improvement in cognitive learning outcomes of grade VI students at SD Negeri 37 Bengkulu City was observed from the pre-cycle activity, where only 13 out of 32 students achieved mastery with a percentage of 40.63%. The average learning outcome achievement in Cycle I increased to a mastery rate of 71.88%, which further increased to 90.63% in Cycle II. The study met the success criteria set by the researchers at 80%, with a final achievement in Cycle II of 90.63%. Therefore, the research process with the implementation of the STAD cooperative learning model was successful and followed the expected procedure.